Labor of Care and Contracts: A Study of Surrogacy after the Transnational Ban in India - Bhardwaj, Ruby (Qualitative Sociology Review, 2025)
Characterized by the interplay of care and contracts, surrogacy is an exclusive form of gendered work. The paper is based on a micro-level ethnographic study exploring the lived and embodied challenges of commercial gestational surrogates in Gujarat, India, who were undertaking surrogacy work after the ban on transnational surrogacy. The experiential accounts collected through in-depth, face-to-face interviews bear the challenges, stigma, and shame involved in surrogacy work. Not only is surrogacy work devalued, deprived of dignity, and shrouded in secrecy, but it is also corrupted by contracts, complicated by alienation and relinquishment of the gestated child. Surrogates disguise their work and stay in surrogacy hostels. Poverty in India compels many women to engage in surrogacy to eke out a living and improve their living conditions. Surrogate mothers are poorly paid, deprived of health benefits and legal security, they receive only twenty percent of the total cost of the surrogacy arrangement, and are also treated as fungible and disposable. The paper adopts the ethics of care perspective to analyze surrogacy arrangements. Such a perspective is directed toward promoting a responsible and humane attitude toward commercial surrogates. It is motivated by the need to uphold the dignity of the surrogates, their legal rights, and the social recognition of their work. The application of care ethics can alleviate the neglect and oppression of surrogates.